Reducing Early Grade Drop Out and Low Learning Achievement in Lao PDR : Root Causes and Possible Interventions - World Bank (World Bank, Washington, DC, 2017)
Participation in basic education in Lao PDR has improved steadily in recent decades. The net enrollment rate for primary schooling has climbed from 65 percent in 1990 to 98 percent in 2014. This increase is a direct result of government policies, with partner support, to build new schools, hire new teachers and improve access to all levels of schooling. It is the result of prioritizing support for specific populations (such as girls and children) who live in rural and remote areas. Also, the increase in the net enrollment rate, combined with the recent decline in the gross enrollment rate (GER), shows that progress is being made in terms of efficiency at the primary level. For lower secondary, the results also show steady increases in both gross and net enrollment rates over the 2000-2014-time period, although much work remains to be done to reach full participation and improved efficiency.